A review of recent advancements in Ni-related materials used for microwave absorption. (16th September 2021) - Wang, Pan; Liu, Dawei; Cui, Liru; Hu, Bo; Han, Xijiang; Du, Yunchen
Abstract: Microwave absorption is emerging as a sustainable pathway through which to alleviate various problems induced by increasingly serious electromagnetic (EM) pollution and interference. As a platform for the conversion of EM energy, microwave-absorbing materials (MAMs) have received widespread attention and have been intensively studied in the past two decades. Among all kinds of materials with characteristic EM functions, the metal Ni has always been regarded as one of the most promising candidates, due to its good magnetic loss, compatible dielectric loss, and high Snoek's limit, as well as its easy production and abundant global reserves. However, it is still difficult for raw Ni particles to realize desirable absorption efficiency, and thus a lot of research has been carried out in the areas of microstructure optimization, alloying, and the composite design of Ni particles to significantly upgrade their microwave absorption performance. This review provides a comprehensive introduction to recent advancements in various high-performance Ni-related MAMs, including hierarchical Ni particles, Ni-based alloy particles, Ni-related composites with metal oxides/sulfides/conductive polymers/various carbon materials, and multicomponent Ni-related composites. Thanks to the synergistic effects between different components and elaborate microstructure designs, these Ni-related MAMs can produce a remarkable improvement in microwave absorption performance. Moreover, the challenges and prospects are also discussed in order to provide some new insights into further research in the field of Ni-related MAMs.